Friends With Benefit Pada Remaja di Kota Makassar - Andi Miranda Ariadna; Andi Ima Kesuma (Rayhan Intermedia, 2023)
This research aims to find out: (1) how teenagers start and live friends with benefits (FWB) relationships in social circles in Makassar City; (2) the impact of the friends with benefits (FWB) phenomenon on teenagers in Makassar City; (3) solution to the friends with benefits phenomenon among teenagers in Makassar City. Data collection techniques are carried out through observation, documentation and interviews. The number of informants in this study was 11 teenagers who lived in Makassar City and had an age range of 17 to 23 years who were or had been involved in friends with benefits (FWB) relationships. Data obtained from research results were processed using qualitative research methods through three stages, namely data reduction, data presentation, and conclusion drawing and verification. Data validation techniques use data triangulation techniques or source triangulation. The research results show that 1. Adolescents starting and undergoing friends with benefits (FWB) relationships in Makassar City are influenced by factors: (1) Adolescent Internal Factors and (2) Adolescent External Factors, which consist of (a) Family Factors (b) ) Adolescent Social Factors (c) Experiencing Problems with Previous Relationships or Relationships that Involve Feelings (d) There are Benefits to be Obtained in a Friends With Benefits Relationship and (e) It's Easy to Start and End a Friends With Benefits Relationship